2013
DOI: 10.1089/apc.2013.0073
|View full text |Cite
|
Sign up to set email alerts
|

Missed Office Visits and Risk of Mortality Among HIV-Infected Subjects in a Large Healthcare System in the United States

Abstract: Linkage and retention in care soon after HIV diagnosis improves clinical outcomes. Conversely, missed visits after diagnosis are associated with increased mortality in the public care setting. We analyzed mortality among newly diagnosed HIV patients ‡ 18 years old in a large private care setting between 01/01/1997 and 12/31/ 2009, comparing patients who missed visits in their first year following diagnosis (index period) with those who did not. Patients who died during the index period were excluded. Hazard ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 26 publications
4
72
1
Order By: Relevance
“…For several opportunistic processes, however, such as central nervous system lymphoma and JC virus encephalitis, survival remains especially poor. These data are in line with reports from other cohorts and jurisdictions [9][10][11][12][13].…”
supporting
confidence: 91%
“…For several opportunistic processes, however, such as central nervous system lymphoma and JC virus encephalitis, survival remains especially poor. These data are in line with reports from other cohorts and jurisdictions [9][10][11][12][13].…”
supporting
confidence: 91%
“…It was previously demonstrated that better retention in HIV care in the first year has been associated with higher rates of ART initiation and improved survival. 26,35,36 Qualitative research would be helpful to develop an understanding of trust in physicians and the healthcare system and of the correlates of retention in HIV care among persons newly diagnosed with HIV infection. Based on our results, one component of interventions designed to improve early retention in care might have a focus on improving trust in physicians.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 To our knowledge, no previous studies have examined the trends in individual VL using complete statewide data. The purpose of our investigation is to examine statewide trends in individual VL over time among PLWHA and identify disparities, if any, by gender, race/ethnicity, age group, HIV risk exposure group, and current residence.…”
Section: Introductionmentioning
confidence: 99%